Global Burden of Dental Caries from 1990 to 2021 and Future Projections - Xiaojing Li; Rui Li; Haozhen Wang; Zurong Yang; Yubo Liu; Xinwei Li; Xin Xue; Shukai Sun; Li-an Wu (International Dental Journal, 2025)
Objective: To characterise the burdens, trends and risk factors of untreated caries in permanent and deciduous teeth from 1990 to 2021 worldwide. Methods: We extracted data on the incidence, prevalence, and years lived with disability (YLDs) due to dental caries from the Global Burden of Diseases Study 2021 for 204 countries and territories between 1990 and 2021. We used the age-standardised rate, percentage change, and estimated annual percentage change to assess the epidemiological characteristics and disease burden. Loess analysis and Spearman correlation were used to explore the associations between the presence of other systemic diseases and caries. A Bayesian Age-Period-Cohort model was further used to predict the burden of caries in the next 3 decades. Results: Totally, there were more cases of caries of permanent teeth (CPT, 2.24 vs 1.46 billion) and caries of deciduous teeth (CDT, 0.52 vs 0.49 billion) globally in 2021 than in 1990. The presence of systemic diseases, such as cardiovascular diseases, diabetes mellitus, enteric infections, oral cancer, and nutritional deficiencies, were significantly associated with the incidence, prevalence and YLDs of CPT. With the growth of global population, the total number of cases of CPT is predicted to reach 2.26 billion by 2050. Conclusions: The incidence of both careis in deciduous teeth and permanent teeth increased over the past 31 years. The risk of developing caries in the permanent dentition is significantly related to the presence of several systemic diseases. Policymakers should implement effective prevention and control strategies to mitigate this major health burden.